The pearl - Steinbeck, John (Penguin London, 2000)
Kino is a Mexican pearl fisher in the Gulf of California. When he and his wife, Juana, have a baby, their joy is complete ... until the infant is bitten by a scorpion. Kino finds a great pearl worth a fortune, but it brings only tragedy and evil to his family